Improved pyroelectric performance for thin film lead zirconate titanate (PZT) capacitors with IrO2 electrodes. (11th December 2015) - Hanrahan, B; Sanchez, L; Waits, C M; Polcawich, R G
Abstract: A four orders-of-magnitude reduction in high temperature leakage current was realized through the use of IrO2 top electrodes in thin film lead zirconate titanate capacitors which has been shown to directly impact the performance of future energy conversion applications. Pyroelectric energy conversion is enhanced near the material Curie temperature, but elevated leakage current in this temperature range hinders current applications. Conductivity experiments varying temperature, composition, and applied bias showed that oxygen vacancy hopping dominates the leakage current in the thin film capacitors above 200 °C. IrO2 top electrodes allow for a reduction in vacancy concentration by allowing for oxygen to be reintroduced during a post-processing annealing step for the thin film. The power lost to leakage current through the pyroelectric conversion cycle is explored. Improvements in remnant polarization and pyroelectric constant are also realized.